Reversible temperature-dependent high- to low-spin transition in the heme Fe–Cu binuclear center of cytochrome ba3 oxidase - Nicolaides, Antonis; Soulimane, Tewfik; Varotsis, Constantinos (My University, 2019)
A reversible temperature-dependent high-spin to low-spin transition with T 1/2 =-60 °C has been observed in the resonance Raman spectra of the equilibrium reduced and photoreduced heme a 3 of the thermophilic ba 3 heme-copper oxidoreductase. The transition is based on the frequency shifts of the spin-state marker bands ν 2 (C b C b ) and ν 10 (C a C m ) and is attributed to the displacement of the heme iron along the heme normal as a consequence of the Fe-Np repulsion at temperature below-40 °C which will increase the ligand field strength forcing the pairing of d electrons into the lower energy orbitals.
Keywords: Barium alloys; Binary alloys; Calcium alloys; Copper alloys